2020
DOI: 10.1177/2158244020983024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographic Burden on Insurance Density

Abstract: The article investigates the relationship between demographic burden and insurance market by employing panel vector autoregression models with six groups of endogenous variables to a dynamic panel data set of 25 economies for the period 1980–2016. Demographic burden is represented by dependency ratios measured in respect to the population younger than the age of 15 (young-age dependency ratio), population above the age of 64 (old-age dependency ratio) as well as males and females above the age of 64 being exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Segodi and Sibindi (2022) suggested that macroeconomic factors are essential drivers of insurance development. For instance, Nebolsina (2020) mentioned that an increasing number of dependents, combined with less favorable economic conditions, harm the affordability of insurance policies. However, according to Lim and Tan (2019), the principal aim of life insurance is to safeguard heirs from financial troubles in the event of a breadwinner's early death.…”
Section: Methodsmentioning
confidence: 99%
“…Segodi and Sibindi (2022) suggested that macroeconomic factors are essential drivers of insurance development. For instance, Nebolsina (2020) mentioned that an increasing number of dependents, combined with less favorable economic conditions, harm the affordability of insurance policies. However, according to Lim and Tan (2019), the principal aim of life insurance is to safeguard heirs from financial troubles in the event of a breadwinner's early death.…”
Section: Methodsmentioning
confidence: 99%